Insurgents in the Province: Tunja, New Granada and the Constitutionalism in the Hispanic world in the decade of 1810 - Uribe Urán, Víctor (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Although its texts usually contain a bigger portion of aspirations of tangible historical realities, for the historians, other humanists and also the dedicated social studies, from an epistemological view, the constitutions constitute worthy “social deeds”, from a methodological view, they also represent “discourse” or “narratives” sensitive and digniied to the analysis of a systematic conceptual and intellectual discussion. These mere circumstances justify once again returning academic attention to them.